9/11 was an Instance of Transnational Balancing: An Intervention in Statist IR Theory. Issue 4 (November 2022) - Aydinli, Ersel
With the end of the Cold War and through the start of the 21st century, conventional IR theories were anticipating an eventual balancing against the United States. Puzzled when this phenomenon did not occur, balancing theorists engaged in a lively discussion, bringing with it the development of proposed alternative forms of balancing and a debate over whether the concept itself had perhaps outlived its relevance. This article reengages with this discussion, suggesting that many of the involved theorists were hampered by theoretical blinders based on statism, and that in fact balancing did occur, but in an unconventional manner and at the hands of an unexpected suspect: al Qaeda, a violent non-state actor, acting in a transnational manner. In this context, this article treats the 9/11 attacks of the violent Jihadist anti-Western movement as an instance of balancing against the hegemon, a successful one in that the Jihadists arguably aimed not at "winning, " but at revealing the superpower's weaknesses so that others would subsequently join the balancing effort. By failing to view the Jihadists' efforts as an ideological balancing effort, the United States responded with force rather than ideational counter-balancing. They waged a war instead of emphasizing efforts to separate the radical violent Jihadist perpetrators from the idea they were championing—a struggle in the name of Muslims/the downtrodden East against the United States—and thus allowing the challenger to rise into a position of "dissident" in the Muslim world, and, arguably, paving the path for today's state revisionist behaviors. The article proposes a framework based on traditionally state-based concepts of intent and impact/capacity to show how non-state actors can in fact balance superpowers and therefore should be incorporated into balancing theories, and presents the actions of the violent Jihadists as an example of transnational, ideational balancing—a phenomenon as real and consequential as state-balancing.